2010
DOI: 10.1210/me.2009-0472
|View full text |Cite
|
Sign up to set email alerts
|

Androgens Induce Nongenomic Stimulation of Colonic Contractile Activity through Induction of Calcium Sensitization and Phosphorylation of LC20 and CPI-17

Abstract: We show that androgens, testosterone and 5alpha-dihydrotestosterone (DHT), acutely (approximately 40 min) provoke the mechanical potentiation of spontaneous and agonist-induced contractile activity in mouse colonic longitudinal smooth muscle. The results using flutamide, finasteride, cycloheximide, and actinomycin D indicate that androgen-induced potentiation is dependent on androgen receptors, requires reduction of testosterone to DHT, and occurs independently of transcriptional and translational events. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 88 publications
2
15
1
Order By: Relevance
“…Our results are in controversy with Gonzáles-Montelongo et al who found that physiological concentrations (10nmol) of testosterone had a stimulating effect on spontaneous contractility in longitudinal colonic smooth muscle of male Swiss CD1 mice [44]. The reason for the contradictory results could be a dose dependent action of TEST: In our study, we used supraphysiological concentrations.…”
Section: Discussioncontrasting
confidence: 69%
“…Our results are in controversy with Gonzáles-Montelongo et al who found that physiological concentrations (10nmol) of testosterone had a stimulating effect on spontaneous contractility in longitudinal colonic smooth muscle of male Swiss CD1 mice [44]. The reason for the contradictory results could be a dose dependent action of TEST: In our study, we used supraphysiological concentrations.…”
Section: Discussioncontrasting
confidence: 69%
“…28 Regarding the relation between DHT and RhoA, a study using mouse colonic longitudinal smooth muscle showed that DHT elicits RhoA activation and translocation to the plasma membrane. 29 Thus, our findings that decreased DHT in the prostate tissue induced low expression of RhoA stand to reason. We suggest that low activity of RhoA may inhibit the contraction of human prostatic smooth muscle and decrease intraurethral pressure.…”
Section: Commentmentioning
confidence: 75%
“…99 Androgens have recently been shown to potentiate ileal and colonic smooth muscle contractions by a non-genomic mechanism involving stimulation of polyamine synthesis which induces calcium sensitization of contractile machinery by ROCK and PKC activation along with increased CPI-17 phosphorylation. 100 Angiotensin IIinduced contractions of rat LES and IAS smooth muscle cells are inhibited by Clostridium botulinum C3 exozyme, HA-1077, and Y-27632, suggesting a role for ROCK. 101 It has been reported that thromboxane A2 and prostaglandin F2α, the end products of the renin-angiotensin system and arachidonic acid pathways, increase IAS tone via activation of RhoA/ROCK and increased MYPT1 T696 and MLC S19 phosphorylation.…”
Section: Inhibition Of Myosin Light Chain Phosphatase Activity By Mypmentioning
confidence: 97%